How Urban Society Can Benefit from Inclusive Mobility - Nikolaus S. Lang; Markus Hagemaier; Pietro Viggiani D'Avalos; Philipp Silvestri (Marketing Review St.Gallen, 2023)
Transportation and economic development are deeply intertwined, with commuting among the greatest indicators of an individual's ability to escape poverty. The latest research collaboration between the Boston Consulting Group, the World Economic Forum and the University of St. Gallen explores how thoughtfully designed mobility systems can play a crucial role in everything from a community's health to socioeconomic gains.
Keywords: 650